China Early Child Development : Early Childhood Education in Yunnan - World Bank (Washington, DC, 2014)
Yunnan is a medium-sized and relatively poor Chinese province on the southwestern border of China. In 2012, the Yunnan department of education formally requested Bank support in conducting a review of early childhood education policies and programs in order to gain an in-depth and evidence-based understanding of the challenges the province faces in expanding early childhood education-in particular to rural and mountainous regions. The Bank's China education team embarked on raising funds, designing and implementing a rather elaborate research agenda around early childhood education. The goal was to investigate key challenges, and to propose policy interventions for expanding the Early Child Development (ECD) coverage in rural Yunnan. This report presents the findings from the background studies, and draws potential policy implications for improving the access to and quality of preschool education in Yunnan province. China has now almost achieved universal 9-year basic education. Over the last decade, the country has devoted increasing attention to policy development in early childhood education. Even though China does not yet have a specific early childhood education law, it has established a rather elaborate set of guidelines and regulations pertaining to early childhood education. Early childhood education has expanded significantly within the last few years. There are two main types of preschool programs for 3-6 year olds including: a regular 3-year program which is called kindergarten, and a one-year program attached usually to primary schools. The rapid growth of preschool teacher supply has contributed to the drop in pupil-teacher ratios across the nation. In Yunnan in particular, the ratio has decreased from approximately 30 to 20 in recent years. However, urban areas still enjoy a more favorable pupil-teacher ratio, as well as a higher proportion of qualified teachers compared to rural areas. Rural areas account for 50 percent of total preschool enrollment, but only 22 percent of all trained teachers serve in rural areas.